#### Answer

$y$ = -$\frac{2}{3}$ , $x$ = $\frac{7}{3}$

#### Work Step by Step

$x$ = $y$ + 3
4($y$ + 3) = $y$ + 10
4$y$ + 12 = $y$ + 10
3$y$ = -2
$y$ = -$\frac{2}{3}$
$x$ = (-$\frac{2}{3}$) + 3
$x$ = $\frac{7}{3}$

Published by
Cengage Learning

ISBN 10:
1-13311-087-8

ISBN 13:
978-1-13311-087-3

$y$ = -$\frac{2}{3}$ , $x$ = $\frac{7}{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.